PROMOTING CULINARY TOURISM : A STUDY IN PANTAI LOSARI - Safina Annajah N Samsudin (Politeknik Pariwisata Makassar, 2025)
This study aims to identify the challenges and opportunities in the management of culinary tourism at Losari Beach, as well as its contribution to the local economy. In addition, the study analyzes effective promotion strategies to enhance the appeal of culinary tourism at Losari Beach in supporting sustainable tourism development in Makassar. This research applies a qualitative method with data collected through direct field observations, documentation as supporting material, and interviews involving tourism managers, local business actors, and visitors as informants. This approach provides a comprehensive picture of how culinary tourism functions not only as a cultural expression but also as a driver of the local economy. The findings reveal that current promotional strategies remain limited, relying mainly on simple social media usage, word-of-mouth, and user-generated content on platforms such as TikTok that occasionally go viral. Although these approaches can increase public awareness, they are inconsistent and unsustainable in reaching a wider audience. Furthermore, several challenges persist, including inconsistency in service quality, hygiene issues, waste management problems, and the presence of street performers, beggars, and people soliciting money in the tourism area. Their presence often causes discomfort among visitors and negatively impacts the overall image of the destination. These conditions highlight the need for more structured promotion strategies and stronger collaboration among stakeholders. Nevertheless, the opportunities for developing culinary tourism at Losari Beach remain significant. Iconic dishes such as pisang epe, complemented by other popular street foods like es pisang ijo, grilled meatballs, and roasted corn, enrich the visitor experience. These culinary offerings not only preserve local food traditions but also contribute to economic activity by supporting small-scale vendors. The strategic location of Losari Beach on the seafront further enhances its appeal, allowing tourists to enjoy dining experiences with a beautiful sunset view. With well-designed promotional strategies, improved service quality, and solutions to existing social challenges, Losari Beach has great potential to strengthen its position as one of Indonesia’s leading culinary tourism destinations.